Program-for-Results : An Early-Stage Assessment of the Process and Effects of a New Lending Instrument - Independent Evaluation Group (World Bank, Washington, DC, 2016)
This evaluation assesses the early experience with the design and implementation of Program for Results (PforR) operations and identifies lessons and recommendations to strengthen this new instrument. When the report was completed in June 2016, none of the PforR programs had closed, and it was too early to draw definitive conclusions in many areas, but the evaluation has brought to light some important insights from the instrument’s early design and implementation experience.